2010
DOI: 10.1111/j.1365-2958.2010.07275.x
|View full text |Cite
|
Sign up to set email alerts
|

SurR regulates hydrogen production in Pyrococcus furiosus by a sulfur-dependent redox switch

Abstract: SummaryWe present structural and biochemical evidence for a redox switch in the archaeal transcriptional regulator SurR of Pyrococcus furiosus, a hyperthermophilic anaerobe. P. furiosus produces H2 during fermentation, but undergoes a metabolic shift to produce H2S when elemental sulfur (S 0 ) becomes available. Changes in gene expression occur within minutes of S 0 addition, and the majority of these S 0 -responsive genes are regulatory targets of SurR, a key regulator involved in primary S 0 response. SurR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 60 publications
(126 reference statements)
1
42
0
Order By: Relevance
“…These enzymes, in combination with SuDH I and SuDH II, may be able to generate amounts of sulfide in NSR1 comparable to those in the parent strain. It has been shown that in the absence of S 0 , SurR activates the transcription of genes necessary for H 2 metabolism and represses that of those required for growth with S 0 (27). Addition of S 0 leads to SurR oxidation, possibly mediated by either colloidal S 0 or polysulfide, such that it is unable to bind DNA (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These enzymes, in combination with SuDH I and SuDH II, may be able to generate amounts of sulfide in NSR1 comparable to those in the parent strain. It has been shown that in the absence of S 0 , SurR activates the transcription of genes necessary for H 2 metabolism and represses that of those required for growth with S 0 (27). Addition of S 0 leads to SurR oxidation, possibly mediated by either colloidal S 0 or polysulfide, such that it is unable to bind DNA (27).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in the absence of S 0 , SurR activates the transcription of genes necessary for H 2 metabolism and represses that of those required for growth with S 0 (27). Addition of S 0 leads to SurR oxidation, possibly mediated by either colloidal S 0 or polysulfide, such that it is unable to bind DNA (27). Since the degree of the SurR-mediated gene regulation was up to 80% lower in the MBX1 and NSR1 deletion strains than in the parent strain (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The native promoter of FHL was replaced with that of the P. furiosus Mbh operon (P mbh1 ), the transcription of which is activated by the SurR regulator during growth in the absence of S 0 , thereby allowing Mbh to catalyze H 2 evolution during sugar fermentation (27,28). A BAC vector was used to facilitate cloning of the construct for chromosomal insertion of the FHL operon ( Fig.…”
Section: Insertion Of the T Onnurineus Fhl Operon Into The P Furiosusmentioning
confidence: 99%
“…MBX is an essential component of the S 0 reduction system, although cells still reduce S 0 in the absence of Nsr (Bridger et al 2011). The metabolic shift between hydrogen and sulfur metabolism, which involves reciprocal regulation of MBH and MBX, is mediated by the transcriptional regulator SurR (Lipscomb et al 2009;Yang et al 2010). The genes encoding hydrogenases and S 0 reduction-related genes together with SurR are a unique and strictly conserved core set of genes in the Thermococcales and form a hallmark of this order (Schut et al 2012a).…”
Section: Hydrogen and Sulfur Metabolismmentioning
confidence: 99%